Pathomorphological Studies on Experimentally Induced Indoxacarb Toxicity and its Amelioration with Vitamin C in Male Wistar Rats - Rathod, Parth B.; Patel, Jasmi G.; Modh, Sneha P.; Raval, Samir H.; Parmar, Rohit S.; Sindhi, Parvez I.; Joshi, Dilip V. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was undertaken to determine the ameliorative effect of vitamin C on indoxacarb induced toxicity in rats. Twenty male Wistar rats were randomly divided into four different groups as I to IV. Rats of Group I, II, III and IV received vehicle carboxymethyl cellulose (control), indoxacarb (173.2 mg/kg b.wt.), vitamin C (200 mg/kg b.wt.) and indoxacarb + vitamin C, respectively, by oral gavages daily for 28 days. Clinical symptoms that were seen in indoxacarb group II rats were also observed in indoxacarb + vitamin C group IV rats, though to a lesser degree. Grossly, stomach was distended and filled with undigested feed materials in Groups II and IV rats. Histopathological changes (degeneration, necrosis and congestion) in the indoxacarb group II were increased when compared to the control group. These microscopic lesions were also visible in the Group IV animals to a lesser extent. In general, vitamin C has ameliorative effect on histopathological changes in indoxacarb intoxicated rats.
Keywords: Amelioration; Indoxacarb; Rats; Toxicopathology; Vitamin C